LEXICAL AND SYNTACTIC-SEMANTIC MEANINGS OF PHRASAL VERBS WITH THE PREPOSITION “ON” - Jumanazarov Samandar Urinovich (European Science Publishing, 2024)
One of the peculiarities of English-language prepositions is that they have the ability to change their function by combining verbs. By combining verbs, they can form certain strings. At the same time, they form complex expressions in combination with certain verbs. The syntactic properties of prepositions are mostly studied in the phrasal layer and the level of the word. The article presents theoretical ideas in this regard and proves them with examples.
Keywords: application; post-prepositions; combinations; outrageous; geometric; grammaticized; syntax; morphological; consideration; foreseeablel.